Analisis Pemilihan Jurusan Siswa Dengan Metode Klasifikasi Algoritma C5.0 (Studi Kasus : SMK Ma’arif Nu Al – Mawardi Bekasi) - Aswan S Sunge (Jurnal SIGMA, 2020)
The study, entitled "Analysis of the Selection of Student Majors with the C5.0 Algorithm Classification Method (Case Study: SMK Ma'arif NU Al - Mawardi Bekasi)" aims to find out information on student majors viewed based on the criteria set by the school using the classification algorithm C5.0 with a decision tree method. The data used in this study were 115 data of students belonging to SMP, with the testing process using Rapid Miner 9.7. Based on the test results of research in predicting majors in junior high school students, from the research using the C5.0 algorithm or decision tree method, the dominant pattern and factor in selecting student majors was obtained, namely based on the value of interest with an accuracy level of 95.65%. So it can be concluded that analyzing the majors of junior high school students at SMK Ma'arif NU Al-Mawardi Bekasi using the C5.0 algorithm classification technique with the decision tree method is considered successful. Keywords : Focusing, SMK, Classification, Algorithm C5.0.